A one-pass variable bit-rate video coding for storage media - Song, Byung Cheol; Chun, Kang Wook (IEEE transactions on consumer electronics, 2003)
The paper presents a one-pass VBR coding algorithm, which provides high visual quality and satisfies a target bit-budget constraint. Since the proposed algorithm exploits the remaining bit amount instead of average bit-rate in determining quantization scale, it can balance the target bit-budget. Simulation results show that the proposed algorithm is superior to the MPEG-2 TM5 constant bit-rate (CBR) control in term of PSNR. The proposed algorithm also achieves real-time VBR video encoding requiring high visual quality for storage media.